An Improved Fracture Criterion for Mixed-Mode Delamination in Composite Materials - Xinyuan Chen; Chengce Yuan; Wei Zhang; Wei Zhang; Weiqiu Chen; Weiqiu Chen; Weiqiu Chen (Aerospace Research Communications)
Delamination is a common failure mode in laminated composites, usually under I/II mixed-mode loading. This paper incorporates the influence of mixed-mode ratio on the critical distance in the fracture criterion based on the minimum strain energy density for delamination failure in composites. Meanwhile, the impact of energy dissipation within the fracture process zone on delamination failure is further considered, leading to an I/II mixed-mode delamination fracture criterion applicable to orthotropic composites. With this novel criterion, the theoretical predictions are in good agreement with experimental data for both natural orthotropic materials and artificial laminated composites. Compared with the traditional mixed-mode fracture criteria based on strain energy density, the new criterion can more accurately capture the experimentally observed “overshoot” phenomenon and is closer to the actual failure situation.